Low-cost catalysts for in-situ improvement of producer gas quality during direct gasification of biomass. (15th December 2018) - Pio, D.T.; Tarelho, L.A.C.; Pinto, R.G.; Matos, M.A.A.; Frade, J.R.; Yaremchenko, A.; Mishra, G.S.; Pinto, P.C.R.
Abstract: In this work, the concept of biomass direct (air) gasification was demonstrated in a pilot-scale bubbling fluidized bed and the influence of in-situ application of low-cost catalytic materials on the produced gas characteristics and gasifier performance was analyzed. Three different low-cost catalysts were tested: bottom bed ashes resulting from combustion of residual forest biomass derived from eucalyptus, char particles resulting from wood pellets direct (air) gasification, and synthetic fayalite (Fe2 SiO4 ). Without using catalysts, the produced gas composition was 7.7–16.9%v CO, 3.2–8.3%v H2, 0.5–3.4%v CH4 and 9.5–14.6%v CO2, with 2.4–4.3 MJ/Nm 3 lower heating value, specific dry gas production between 1.0 and 1.8 Nm 3 dry gas/kg biomass (dry basis), cold gas efficiency between 13.7 and 30.5% and carbon conversion efficiency between 30.7 and 50.9%. With the use of catalysts, the produced gas composition was 14.2–37.6%v CO, 9.5–14.7%v H2, 2.6–3.5%v CH4 and 3.6–14.8%v CO2, with 3.9–6.3 MJ/Nm 3 lower heating value, specific dry gas production between 1.4 and 2.0 Nm 3 dry gas/kg biomass (dry basis), cold gas efficiency between 38.1 and 66.3% and carbon conversion efficiency between 56.8 and 86.6%. The highest increase in H2 concentration (352% increase) was observed on experiments using wood pellets char as catalyst while the highest increase in CO (305% increase), lower heating value (123% increase), specific dry gas production (62% increase), cold gas efficiency (262% increase) and carbon conversion efficiency (174% increase), was observed on experiments using synthetic Fe2 SiO4 as catalyst. Highlights: Low-cost catalyst as primary measure to improve gas quality in biomass gasification. Novel system configuration to assess catalyst performance in a pilot-scale gasifier. Wood pellets chars as catalysts significantly improve H2 yield. Fe2 SiO4 as catalysts significantly improve CO yield and efficiency parameters.